Primary science. (Hatfield : Association for Science Education)
Primary science aims to share information and ideas that support effective practice in science education focused at the primary school level through transition to early secondary education. Many of the articles are therefore relevant to both primary and secondary phases of education. It includes articles, both requested and unsolicited, about teaching, learning and assessing science for all children in the 3 - 12 year age range.Topics covered include selecting, adapting and managing learning activities both within and outside the classroom, research findings, adaptations for children with special needs, health and safety, use of ICT, links to other areas of the curriculum and information about useful books, equipment, audio-visual aids, websites and CDRoms. Insights into familiar classroom activities are included, as are articles containing novel ideas about content and teaching and learning processes. The articles are reflective rather than purely descriptive, as they focus on the impact on the learners, so contributions from classroom practitioners are encouraged.
Doorlopende nummering.
Verschijnt 5 maal per jaar.
Keywords: Onderwijs -- Tijdschriften